PROGRAM ENGLISH FOR KIDS: PELATIHAN PERCAKAPAN BAHASA INGGRIS BAGI ANAK USIA SD DI YAYASAN PANTI ASUHAN PENUH PENGHARAPAN MEDAN - Pioro Benevolent Lariest; Bertova Simanihuruk; Anselmus C. A. Bangun; Rosa Maria Simamora; Bonar Gurning (Yayasan Education and Social Center, 2026)
This community service program aimed to improve the English speaking skills of elementary school children at Yayasan Panti Asuhan Penuh Pengharapan Medan. The program, titled